Holder of lightning - Farrell, S. L. (Stephen Leigh), 1951- (Farrell, S. L. (Stephen Leigh), 1951- Cloudmages, 2004)
Jenna, a seventeen-year-old farm girl, finds her life forever altered when she touches a small, yet strangely enthralling stone that awakens a powerful ancient magic, putting her life, as well as the lives of her family and friends, in grave danger.